Return on investment from educational research grant funding: deliverables and measurement - Ahmad Taufek Abdul Rahman; Mohd Hafiz Hanafiah; Umi Marshida Abd Hamid; Nor Azura Md Ghani; Nur Adilah Md Zain (Institute of Advanced Engineering and Science, 2024)
This paper investigates the return on investment (ROI) paradigm from fundamental educational research grant funding perspectives. The researchers conducted a wide-ranging literature search regarding the educational research grant funding ROI from public policy and economics viewpoints. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) were utilized to identify and analyze research articles and original reports related to ROI from educational research grant funding. The research data were screened through a literature review based on the inclusion criteria, namely study focusing on return on investment of educational research funding and study published between 2001 and 2021 (as of December 2022). This study found evidence that ROI calculation from fundamental educational research grants is not straightforward and varies. Besides, most available research focuses on research impact rather than economic and intrinsic research value. Based on the compiled literature on research-related performance attributes, this study identified three distinct deliverables of educational research funding: tangible output, intangible output, and research outcome. The present research proposes more robust and reliable methods for measuring the ROI of fundamental educational research impact, potentially generating a much-inform decision-making and resource allocation in educational research grant funding.